2020
DOI: 10.3390/w12102806
|View full text |Cite
|
Sign up to set email alerts
|

Water Level Fluctuations and Air Temperatures Affect Common Reed Habitus and Productivity in an Intermittent Wetland Ecosystem

Abstract: Lake Cerknica is an intermittent wetland ecosystem with extreme water level fluctuations. It hosts extensive reed stands that have colonized different habitat types. Two different stands were compared: a lake stand not directly influenced by the intermittent River Stržen and a riparian stand near River Stržen. Reed productivity (growth and assimilate allocation) was monitored for these reed stand types over 13 years (2007–2019), and this measurement was compared to monthly water levels and air temperatures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Similarly, Wirsel et al [ 65 ] observed Sclerotinia on the Phragmites material only in flooded sites. Flooding can induce leaf senescence and programmed cell death [ 66 ], which is frequently the case in the studied wetland [ 4 ]. As preventing early senescence is a resistance strategy of plants against necrotrophs [ 67 ], the faster senescence of leaves could speed up nutrient acquisition by necrotrophs and improve their spread in early phases of leaf decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wirsel et al [ 65 ] observed Sclerotinia on the Phragmites material only in flooded sites. Flooding can induce leaf senescence and programmed cell death [ 66 ], which is frequently the case in the studied wetland [ 4 ]. As preventing early senescence is a resistance strategy of plants against necrotrophs [ 67 ], the faster senescence of leaves could speed up nutrient acquisition by necrotrophs and improve their spread in early phases of leaf decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…The level of herbivory in such wetlands is relatively low, thus the majority of produced biomass is subjected to the decomposition processes [ 2 ]. Phragmites australis is a highly productive cosmopolitan species that forms extensive monoculture stands in many wetlands [ 1 ] and contributes significantly to plant litter production in these ecosystems [ 3 , 4 ]. Leaf litter has multiple functions in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The association Potamo crispi-Ranunculetum trichophylli is the only association from this alliance. It encompasses the vegetation of aquatic plants, that is mainly present in rivers on karst poljes with an extremely fluctuating water table [101].…”
Section: Plant Communitiesmentioning
confidence: 99%
“…A hydrological gradient and a fluctuating water level present major driving forces, which determine the distribution of different plant communities as well as plant species composition within them. This was evidenced in various aquatic ecosystems, such as wet-meadows [12], marshes [4], intermittent lake [15], flood-forests [11], ponds [10], lakes [3,17], or rivers [6]. Waterlogged or flooded soil can become an inhospitable environment, which excludes the majority of species, while in the remaining species, it triggers the expression of various traits and mechanisms that enable survival despite oxygen shortage in the root zone.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of Gaberščik et al [15] analyzes the long-term response of cosmopolitan species Phragmites australis to extreme water level fluctuations. The study was performed in intermittent wetland Lake Cerknica, which is located at the bottom of the Cerkniško polje depression.…”
Section: Main Messages Of This Special Issuementioning
confidence: 99%